Robotic Process Automation in Small and Medium-sized Businesses: Potential Benefits and Challenges - Hanhisalo, Erica (My University, 2026)
This study addresses the application of Robotic Process Automation (RPA) in small and medium sized enterprises (SMEs). Automation, the use of machines and computers to streamline the production of goods and services, has evolved into RPA. A technology that is designed to automate repetitive, rule-based tasks by mimicking human interactions with digital systems. While there is substantial research on RPA in large enterprises, this paper aims to fill the literature gap concerning its use in SMEs. The research objective was to investigate the applicability of RPA in SMEs, specifically focusing on the potential benefits and challenges of implementation. The study was conducted as a narrative literature review, utilizing ACM Digital Library and IEEE Xplore Digital Library as primary academic databases. The search was limited to publications from the last 10 years and 13 articles focusing on RPA implementation in small and medium businesses were evaluated. The research successfully identified multiple potential benefits and challenges associated with RPA adoption in SMEs. The most considerable benefits are efficiency and error reduction. RPA robots can operate 24/7, executing tasks rapidly and minimizing human error caused by factors like tiredness. Efficiency gains can be significant, potentially reaching 60-80% time savings in human resources, order-to-cash and finance processes. Furthermore, RPA achieved 99.9% accuracy in accounting tasks compared to approximately 90% for traditional human labor, reducing errors from manual data entry and transfer. These benefits contribute to cost reductions/savings, as an RPA solution can cost as little as one-fifth the price of a full-time employee performing the same task. RPA also has easy integration compared to traditional automation, as it works at the user interface level, making it a potentially viable and cost effective option for SMEs. The most considerable challenges identified are selecting the right process and integration. RPA projects have a failure rate of 30% to 50%, highlighting the necessity of thorough analysis to identify suitable processes to be automated. Integration can be challenging due to the robot’s dependency on the Graphical User Interface (GUI), where UI changes can cause the robot to fail. Additionally, maintaining data integrity is a concern, as there have been instances where RPAs misinterpret data or struggle with system navigation and errors in data extraction and processing can dilute efficiency gains. The research objective was achieved, providing SMEs with a balanced understanding of RPAs impact. A practical recommendation is that SMEs thoroughly consider if suitable processes exist for RPA implementation and run small-scale pilot programs to test how well RPA fits the company’s needs and infrastructure. As well as mitigate risks, particularly those related to data integrity and GUI instability.

Tutkimus käsittelee robottiprosessiautomaation (RPA) soveltamista pienissä ja keskisuurissa yrityksissä (pk-yritys). Automaatio, eli koneiden ja tietokoneiden käyttö tavaroiden ja palveluiden tuotannon tehostamiseen, on kehittynyt RPA:ksi. Teknologia, joka on suunniteltu automatisoimaan toistuvia, sääntöihin perustuvia tehtäviä matkimalla ihmisen vuorovaikutusta digitaalisten järjestelmien kanssa. Vaikka RPA:ta on tutkittu laajasti suuryrityksissä, tämän tutkimuksen tavoitteena on täyttää kirjallisuudessa oleva aukko sen käytöstä pk-yrityksissä. Tutkimuksen tavoitteena oli tutkia RPA:n sovellettavuutta pk-yrityksissä keskittyen erityisesti käyttöönoton mahdollisiin hyötyihin ja haasteisiin. Tutkimus toteutettiin narratiivisena kirjallisuuskatsauksena hyödyntäen ACM Digital Librarya ja IEEE Xplore Digital Librarya ensisijaisina akateemisina tietokantoina. Haku rajoitettiin viimeisten kymmenen vuoden julkaisuihin, ja arvioitiin 13 artikkelia, jotka keskittyivät RPA:n käyttöönottoon pienissä ja keskisuurissa yrityksissä. Tutkimuksessa tunnistettiin useita potentiaalisia hyötyjä ja haasteita, jotka liittyvät RPA:n käyttöönottoon pk-yrityksissä. Merkittävimmät hyödyt ovat tehokkuus ja virheiden vähentäminen. RPA-robotit voivat toimia ympäri vuorokauden, suorittaa tehtäviä nopeasti ja vähentää inhimillisten virheiden määrää. Tehokkuuden parannukset voivat säästää jopa 60–80 % ajasta tietyissä tehtävissä. Lisäksi RPA saavutti 99,9 %:n tarkkuuden kirjanpitotehtävissä verrattuna ihmistyön noin 90 %:iin, mikä vähentää manuaalisesta tiedonsyötöstä aiheutuvia virheitä. Tämä mahdollistaa kustannussäästöjä, sillä RPA-ratkaisun kustannukset voivat olla noin viidenneksen kokopäiväisen työntekijän kustannuksista Lisäksi RPA on perinteiseen automaatioon verrattuna helppo integroida, koska se toimii käyttöliittymätasolla, mikä tekee siitä kustannustehokkaan vaihtoehdon pk-yrityksille. RPA:n keskeisimpiä haasteita ovat sopivien prosessien valinta ja integraatio. RPA-projektien epäonnistumisprosentti on 30–50 %, mikä korostaa huolellisen prosessianalyysin merkitystä. Integraatio voi olla haastavaa, koska robotit ovat riippuvaisia graafisista käyttöliittymistä, ja käyttöliittymämuutokset voivat aiheuttaa toimintahäiriöitä. Lisäksi tiedon eheyden varmistaminen on haaste, sillä virheet tiedon tulkinnassa ja käsittelyssä voivat heikentää saavutettuja tehokkuushyötyjä. Tutkimuksen tavoite saavutettiin, ja se tarjoaa pk-yrityksille tasapainoisen kuvan RPA:n vaikutuksista. Käytännön suosituksena on, että pk-yritykset arvioivat huolellisesti, löytyykö organisaatiosta RPA:lle soveltuvia prosesseja, ja toteuttavat pienimuotoisia pilottihankkeita testatakseen, miten hyvin RPA sopii yrityksen tarpeisiin ja infrastruktuuriin. Lisäksi suositellaan riskien hallintaa, erityisesti tietojen eheyteen ja käyttöliittymän vakauteen liittyvien riskien osalta.
Keywords: small and medium-sized enterprises; fi=Automaatio- ja tietotekniikka|en=Automation and Computer Science|; fi=Energia- ja informaatiotekniikan ohjelma|en=Degree Programme in Energy Technology and Information Technology|